If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -3) + 8 = 5xd + -22 Reorder the terms: 8(-3 + x) + 8 = 5xd + -22 (-3 * 8 + x * 8) + 8 = 5xd + -22 (-24 + 8x) + 8 = 5xd + -22 Reorder the terms: -24 + 8 + 8x = 5xd + -22 Combine like terms: -24 + 8 = -16 -16 + 8x = 5xd + -22 Reorder the terms: -16 + 8x = -22 + 5dx Solving -16 + 8x = -22 + 5dx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5dx' to each side of the equation. -16 + -5dx + 8x = -22 + 5dx + -5dx Combine like terms: 5dx + -5dx = 0 -16 + -5dx + 8x = -22 + 0 -16 + -5dx + 8x = -22 Add '16' to each side of the equation. -16 + -5dx + 16 + 8x = -22 + 16 Reorder the terms: -16 + 16 + -5dx + 8x = -22 + 16 Combine like terms: -16 + 16 = 0 0 + -5dx + 8x = -22 + 16 -5dx + 8x = -22 + 16 Combine like terms: -22 + 16 = -6 -5dx + 8x = -6 Reorder the terms: 6 + -5dx + 8x = -6 + 6 Combine like terms: -6 + 6 = 0 6 + -5dx + 8x = 0 The solution to this equation could not be determined.
| -6+(-3x)=x+6 | | (4/5)x-3=-11 | | (1/4)x+1=0 | | 3x+7=-52-9x | | (1/3)x+2=-2 | | 2lnx=ln(8x+3) | | (3/5)x+7=7 | | y=(1/x+2)+3 | | (3/4)x+1=10 | | y=-x^2+3x-2 | | (2/3)x-1=3 | | (4a-7)/3 | | 4z-7z=-21 | | 85+x=197 | | -4+m=9 | | 6j-2=4j+14 | | 2xy+2xy-xy= | | x=16+x/x-3 | | 2m^2-3m+4m^2-3m^3= | | w=12.8/8 | | 4x*2-49= | | 6x*2-23x-4= | | 98-6x=30x+18 | | 4-3x=-4x | | -(8p-23)=55 | | -(14-7b)=-49 | | x*2-121= | | 6x*2+x-12= | | 2xy+5y-7=0 | | 3-2(x+2)=7 | | 2(x-6)-4(x+2)=-6 | | 0.66x-2=3 |